2013
DOI: 10.1002/stem.1308
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Human Pluripotent Stem Cell Models of Fanconi Anemia Deficiency Reveal an Important Role for Fanconi Anemia Proteins in Cellular Reprogramming and Survival of Hematopoietic Progenitors

Abstract: Fanconi anemia (FA) is a genomic instability disorder caused by mutations in genes involved in replicationdependant-repair and removal of DNA cross-links. Mouse models with targeted deletions of FA genes have been developed; however, none of these exhibit the human bone marrow aplasia. Human embryonic stem cell (hESC) differentiation recapitulates many steps of embryonic hematopoietic development and is a useful model system to investigate the early events of hematopoietic progenitor specification. It is now p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
2
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 34 publications
4
37
2
1
Order By: Relevance
“…Previous studies have indicated that FA proteins are required for normal hematopoiesis and hematopoietic progenitor cell (HPC) survival (6)(7)(8)18). To evaluate whether REV7 deficiency can affect hematopoiesis, we silenced this gene in mouse HPCs.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that FA proteins are required for normal hematopoiesis and hematopoietic progenitor cell (HPC) survival (6)(7)(8)18). To evaluate whether REV7 deficiency can affect hematopoiesis, we silenced this gene in mouse HPCs.…”
Section: Resultsmentioning
confidence: 99%
“…46 Although we have not studied in detail whether NHEJ is activated during the reprogramming process; the much lower efficiency of obtaining iPSC from LIG4-NHEJ-deficient fibroblasts together with accumulation of chromosomal abnormalities during the reprogramming of those lines, suggest that activation of NHEJ may also be required in this process. Muller et al 47 have shown that reprogramming induces DNA damage, resulting in upregulation of p53, increased DSBs and senescence.…”
Section: Discussionmentioning
confidence: 95%
“…Because FA fibroblasts are difficult to reprogram, this study uncovered a novel role of the FA pathway in cell reprogramming. Consequently, correcting FA genes restores the reprogramming efficiency of FA fibroblasts to IPS cells [93][94][95][96][97][98]. Reprogramming induces the DDR [99] and activates the FA pathway [94], leading to P53-mediated apoptosis and low reprogramming efficiency [96].…”
Section: Novel Therapies: From Genes To Patientsmentioning
confidence: 99%